THE STUDENTS’ ABILITY IN UNDERSTANDING DESCRIPTIVE ESSAY - Destri Wahyuningsih; Dian Al-Fajri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The purpose of this research is to find out the students’ ability in understanding descriptive essay at Second Semester Students of STKIP Insan Madani Airmolek. The researcher used Descriptive Analysis Research. In this research, researcher wants to describe the students’ ability in understanding descriptive essay. This research used the formulation total percentage of the result students ability descriptive essay and describe the result in understanding descriptive essay. The students’ ability tests answer include all meeting their score of the test result were fair is 57%. The result in understanding descriptive essay are most of the students got less in understanding descriptive essay, two students got fair criterion, and two students got fair good criterion.